Aerodynamic Interactions of Side-by-Side Rotors in Ground Proximity - Dekker, H.N.J.; Ragni, D.; Baars, W.J.; Scarano, F.; Tuinstra, M. (AIAA, 2022)
An experimental investigation is conducted to study the aerodynamic behavior of a two-rotor system in ground proximity. The counter-rotating rotors are placed side-by-side in the hovering condition. The time-averaged and unsteady flow behavior is studied when the rotor-to-rotor lateral distance and the distance between the rotors and the ground are varied. The experiments are performed using three-dimensional large-scale volumetric velocimetry with helium-filled soap bubbles as tracers, tracked by the particle motion analysis technique “Shake-The-Box.” The mean velocity field reveals the wake deflection due to the ground plane and the formation of toroidal-shape regions of separated flow below each rotor. The interaction of the wall jets formed by slipstream deflection results in a separation line with the flow emerging from the wall in a fountain-like pattern. Regimes of flow re-ingestion occur when the rotors are sufficiently far apart. The flowfield exhibits the tendency toward asymmetric states, during which the fountain flow column and the domain of re-ingestion shift closer to one of the rotors. A generic classification of flow regimes is proposed in relation to the behavior of two rotors in ground effect.
This article has been correctedERRATUMCorrection: Aerodynamic Interactions of Side-by-Side Rotors in Ground Proximity